Comparative toxicology of extracts of Guava (Psidium Guajava L.) leaves on Artemia Salina Nauplii, human colon cancer cell line HCT116, and human bone marrow mesenchymal stem cells - MOSTRALES, DEO CHARIS (Archīum Ateneo, 2017)
Different parts of the guava plant (Psidium guajava L.) are used in diverse ethnomedical applications by tropical cultures wherever it is found. While there has been a growing interest for scientific techniques to verify the claims of traditional medicine, there is also a corresponding concern for the safety of herbal products used for therapeutic applications. For this purpose, serially-fractionated ethanolic guava leaf extracts were subjected to a primary screen of brine shrimp (Artemia salina) lethality test and MTT assays on HCT116 (human colon cancer) and BMMSC (human bone-marrow-derived stem cells) complemented by a TLC phytochemical profiling. Results show that the trends in the MTT assays of HCT116 and BMMSC correspond (correlating the LC50 logarithms yields r = 0.81) whereas the brine shrimp lethality test differs from both (r = 0.37 versus HCT116, r = 0.035 versus MSC). Additionally, there is particular interest in the ethyl acetate fraction which contains alkaloids, terpenoids, and flavonoids, and which exhibits considerably more bioactivity in the live organisms (LC50 = 102.92 ppm) than the human cells (BMMSC LC50 = 762.54 ppm), implying that the bioactivity of constituents in the fraction involve systemic effects that are absent in the metabolism of HCT116 and BMMSC. The specific mechanisms of the divergent toxicities of the in vivo to the in vitro models accounting for the different pharmacokinetics of human and aquatic invertebrate subjects and for the protein-drug conjugates and intersystem signaling in whole organisms need further investigation.